Formation of 1, 3‐Cyclohexanediones and Resorcinols Catalyzed by a Widely Occuring Ketosynthase1. Issue 15 (19th February 2013) - Fuchs, Sebastian W.; Bozhüyük, Kenan A. J.; Kresovic, Darko; Grundmann, Florian; Dill, Veronica; Brachmann, Alexander O.; Waterfield, Nicholas R.; Bode, Helge B.
<x xml:space="preserve">Abstract</x> Overlooked, but widespread! A new class of ketosynthases (DarB) involved in the biosynthesis of 1, 3‐cyclohexanediones and dialkylresorcinols has been identified and characterized in detail. The presence of homologues in 89 different bacteria, including several pathogens, reveals that DarB as well as the corresponding natural products might be widespread, thus presenting a new but so far overlooked pathway to natural products.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>